Reducing the costs of producing electric energy by using the concentrated solar energy technology (Journal of Accounting and Financial Studies ( JAFS ), 2023)
The aim of this research is to highlight the importance of reducing the costs of producing electric energy by using concentrated solar energy technology, to encourage the trend towards investment in clean energy, to raise the level of production efficiency of electric energy and to fill the shortage in all energy production companies, and at the level of the general / regional company in particular. In order to achieve the desired goals of the current research, it was applied in the General Company for Electric Power Production / Central Region for 2019 data, which is one of the formations of the Iraqi Ministry of Electricity, as it includes a group of energy-producing stations that use fossil fuels in their operation, represented by stations (steam, diesel, gas) and also Hydroelectric power stations, which are represented by the stations (Hamrin Dam and Haditha Dam), but the data of the hydroelectric power stations were not taken, as they are environmentally friendly energy, and only the fossil fuel power stations were targeted.